2010
DOI: 10.1111/j.1600-6143.2010.03331.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver and Vascularized Posterior Rectus Sheath Fascia Composite Tissue Allotransplantation

Abstract: Abdominal wall closure in pediatric solid organ recipients may be confounded by donor size discrepancy and structural insults from previous surgery. Here we describe the novel use of vascularized donor abdominal wall posterior rectus sheath fascia, as a composite tissue allotransplant (CTA), to achieve abdominal wall closure in a liver and double kidney pediatric recipient who could not be closed primarily due to donor/recipient size mismatch. The posterior rectus sheath fascia was procured in continuity with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 18 publications
(22 reference statements)
0
29
0
Order By: Relevance
“…Closure of 16 visceral transplant patients with nonvascularized rectus fascia resulted in wound infections in half and herniation in one case . Vascularized posterior rectus fascia taken in continuity with the liver graft receiving its blood supply via the hepatic artery has been reported in three cases with short‐term success in the first case and longer‐term success in the other two, although in one of these cases the rectus fascia was not substantial enough to close the abdominal defect without a synthetic mesh, and this patient required re‐operation on two occasions to plicate the rectus fascia and to remove the mesh .…”
Section: Discussionmentioning
confidence: 99%
“…Closure of 16 visceral transplant patients with nonvascularized rectus fascia resulted in wound infections in half and herniation in one case . Vascularized posterior rectus fascia taken in continuity with the liver graft receiving its blood supply via the hepatic artery has been reported in three cases with short‐term success in the first case and longer‐term success in the other two, although in one of these cases the rectus fascia was not substantial enough to close the abdominal defect without a synthetic mesh, and this patient required re‐operation on two occasions to plicate the rectus fascia and to remove the mesh .…”
Section: Discussionmentioning
confidence: 99%
“…12 Finally, vascularized posterior rectus sheath has been reported in three cases with short-term success, although less is known about the structural integrity of the graft in long-term follow-up. 15,16 Furthermore, there are concerns about the size of the graft when used to reconstruct larger, full-thickness defects. …”
Section: Discussionmentioning
confidence: 99%
“…64 In combination with liver transplants, the posterior rectus sheath has also been transplanted successfully to aid closure of the abdomen. 65,66 Preclinical studies have investigated the utility of abdominal wall transplant to aid closure, in the absence of a concomitant visceral transplant. 63,67 Although this procedure is technically feasible, it cannot be justified currently because studies have not shown restoration of abdominal wall function and the requirement for long-term immunosuppression is an issue of concern.…”
Section: Vca In Other Areasmentioning
confidence: 99%